Polymorphisms of the TAP1 and TAP2 transporter genes in Japanese SLE. Issue 12 (December 1996) - Takeuchi, F; Nakano, K; Nabeta, H; Hong, G H; Kuwata, S; Ito, K
Abstract : OBJECTIVE: To determine how polymorphism of transporter associated with antigen processing 1 and 2 (TAP1 and 2) alleles contributed to the pathogenesis of systemic lupus erythematosus (SLE) in Japanese patients. METHODS: TAP1 and TAP2 typing was carried out in 52 Japanese patients with SLE and 95 normal subjects by the PCR-RFLP (restriction fragment length polymorphism) method. HLA-DR typing and HLA-DRB1*15 genotyping were carried out by the PCR method and PCR-SSCP (single stranded DNA conformation polymorphism) method, respectively. RESULTS: No particular TAP 1 allele was associated with Japanese SLE or with immunological subgroup of SLE. TAP2H showed a tendency towards increased frequency in SLE (5.8% v 0% in control), but the corrected P value was not significant. No other particular association of TAP2 allele was observed. Furthermore, these was no evidence for linkage disequilibrium between any TAP1/TAP2 alleles and HLA-DRB1*1501--which is reported to be weakly but significantly association with Japanese SLE--in either the normal control or the SLE patient group. CONCLUSIONS: Neither the TAP1 nor the TAP2 gene appears to determine disease susceptibility to SLE in Japanese, and these results are in keeping with those reported in Caucasian SLE patients.